Sensing the Present: “Conceptual Art of the Senses” - Bal, Mieke; Burke, Rachel E. (Text Matters: A Journal of Literature, Theory and Culture, 2017)
After Rachel E. Burke briefly introduces the essays presented with a focus on our contemporary relationship to modern subjectivity, Mieke Bal will make the case for the sense of presentness on an affective and sensuous level in Munch’s paintings and Flaubert’s writing by selecting a few topics and cases from the book Emma and Edvard Looking Sideways: Loneliness and the Cinematic, published by the Munch Museum in conjunction with the exhibition Emma & Edvard. It is this foregrounded presentness that not only produces the ongoing thematic relevance of these works, but more importantly, the sense-based conceptualism that declares art and life tightly bound together. If neither artist eliminated figuration in favour of abstraction, they had a good reason for that. Art is not a representation of life, but belongs to it, illuminates it and helps us cope with it by sharpening our senses. As an example, a few paintings will clarify what I mean by the noun-qualifier “cinematic” and how that aesthetic explains the production of loneliness.